Blow-Out Fracture of Orbit (Reconstructed with Stent Campo) - P. A. Lamba; A. K. Gupta; K. N. Shukla (Indian Journal of Plastic Surgery)
A case of blow-out fracture of the orbit with herniation of the globe into the maxi-Hary antrum is presented. The floor was reconstructed using Stent campo with satisfactory repair and without any undue reaction to the compound. The literature of blow-out fractures is briefly reviewed. The use of Stent campo for repair of floor ol orbit is recommended as an emergency or temporary measure.